Invasive splenic mucormycosis due to Rhizopus microsporus during chemotherapy for acute monocytic leukemia: a case report and literature review - Peng, Xiru; Wei, Zixiu; Wang, Lijuan; Cheng, Juan (Frontiers in Oncology, 2023)
Mucormycosis is a rare opportunistic fungal infection associated with high mortality and occurs typically in immunocompromised patients. It is difficult to diagnose owing to non-specific clinical manifestations, serological index, imaging features, and limitations of diagnostic methods. The incidence of invasive splenic mucormycosis is extremely rare, with only a few cases documented in the literature.We report a survival case of invasive splenic mucormycosis involving the liver caused by Rhizopus microsporus in a patient during consolidation therapy with acute monocytic leukemia (AML-M5). The patient initially presented with recurrent fever and splenomegaly accompanied by multiple focal hypo-densities unresponsive to empirical anti-infection treatment. Splenic mucormycosis was diagnosed by Contrast-Enhanced Ultrasonography (CEUS) and metagenomic next-generation sequencing (mNGS). However, surgical intervention carries a high risk due to the progressive involvement of the liver in invasive splenic mucormycosis. Fortunately, monotherapy with amphotericin B is effective, and the patient has undergone allo-HSCT. This case aims to emphasize the importance of utilizing mNGS and CEUS in the timely diagnosis of mucormycosis to help clinicians identify splenic mucormycosis and take appropriate therapy as soon as practicable, to improve therapeutic efficacy and prognosis.